2000
DOI: 10.1152/ajpregu.2000.278.6.r1453
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of neuronal nitric oxide synthase, NOS I, in the developing porcine kidney

Abstract: To determine if the developing kidney differs from the adult in the expression of the neuronal nitric oxide synthase, NOS I, these experiments measured mRNA gene expression by RNase protection assay and protein content by Western blot of NOS I in piglets at ages newborn and 3, 7, 10, 14, and 21 days and adult pigs. Whole kidney NOS I mRNA was greatest at birth and decreased progressively during renal maturation to adult levels. NOS I protein content paralleled this developmental pattern. Cortical NOS I protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
36
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 40 publications
7
36
0
1
Order By: Relevance
“…An alternative explanation is that there is an age-dependent effect of endogenously produced NO on net filtration pressure through its vasodilatory effects on afferent arteriolar tone. This premise is supported by an age-dependent distribution of renal nNOS mRNA gene expression and localization (11,35,37). Furthermore, Kullaprawithaya et al (21), using elegant laser capture microdissection techniques, recently reported that macula densa nNOS mRNA gene expression is greater in newborn piglets than older pigs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An alternative explanation is that there is an age-dependent effect of endogenously produced NO on net filtration pressure through its vasodilatory effects on afferent arteriolar tone. This premise is supported by an age-dependent distribution of renal nNOS mRNA gene expression and localization (11,35,37). Furthermore, Kullaprawithaya et al (21), using elegant laser capture microdissection techniques, recently reported that macula densa nNOS mRNA gene expression is greater in newborn piglets than older pigs.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the renal distribution of NOS is also developmentally regulated. For example, Solhaug et al (35) measured renal nNOS mRNA gene expression in piglets and adult pigs and observed a greater nNOS mRNA in immature compared with mature kidneys. In guinea pigs, Thompson and Weiner (37) found that NOS activity increased during fetal life to reach maximal levels in the newborn kidney, decreasing thereafter.…”
mentioning
confidence: 99%
“…During the newborn's period of increased NO production, eNOS expression is minimally detectable, with protein levels sevenfold less than what is observed in the adult (20). However, nNOS expression in whole-kidney models and in microdissected preglomerular resistance vessels is significantly enhanced in the newborn and strongly suggests that the nNOS isoform, and not eNOS, is the major NOS isoform contributing NO to the newborn's renal hemodynamic state (3,19,20).…”
Section: Discussionmentioning
confidence: 94%
“…NO is known to inhibit cyclic adenosine monophosphate degradation through cyclic GMP-mediated mechanisms, thereby stimulating renin secretion, whereas cellular calcium influx and protein kinase K activation inhibit renin release (36 (3,11,19). In studies by Ratliff et al, it was demonstrated that NO production in the preglomerular resistance vasculature is threefold higher in the newborn than in the adult (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation